Accumulation of polycyclic aromatic hydrocarbons (PAHs) and oxygenated PAHs (OPAHs) in organic and mineral soil horizons from four U.S. remote forests. (September 2015) - Obrist, Daniel; Zielinska, Barbara; Perlinger, Judith A.
Highlights: PAH and OPAH concentrations increase from surface litter to humidified litter layers in forests. PAHs and OPAHs significantly accumulate in forest litter and soils. Prescribed fires enhance PAHs concentrations in forest litter horizons. OPAHs show stronger accumulation than PAHs in forest litter and soils. OPAHs and PAHs strongly associate with old decomposed carbon pools in forests. Abstract: We characterized distributions of 23 polycyclic aromatic hydrocarbons (Σ23PAH) and nine oxygenated PAHs (Σ9OPAH) in four remote forests. We observed highest Σ23PAH and Σ9OPAH concentrations in a coniferous forest in Florida, particularly in organic layers which we attributed to frequent prescribed burning. Across sites, Σ23PAH and Σ9OPAH concentrations strongly increased from surface to humidified organic layers (+1626%) where concentrations reached up to 584 ng g −1 . Concentrations in mineral soils were lower (average 37 ± 8 ng g −1 ); but when standardized per unit organic carbon (OC), PAH/OC and OPAH/OC ratios were at or above levels observed in organic layers. Accumulation in litter and soils (i.e., enrichment factors with depth) negatively correlated with octanol–water partition coefficients ( K ow ) and therefore was linked to water solubility of compounds. Concentrations of Σ9OPAHs ranged from 6 ± 6 ng g −1 to 39 ± 25 ng g −1 in organic layers, and from 3 ± 1 ng g −1 to 11 ± 3 ng g −1 in mineral soils, and were significantly and positively correlated to Σ23PAHs concentrations ( r 2 of 0.90) across sites and horizons. While OPAH concentrations generally decreased from organic layers to mineral soil horizons, OPAH/OC ratios increased more strongly with depth compared to PAHs, in particular for anthrone, anthraquinone, fluorenone, and acenaphthenequinone. The strong vertical accumulation of OPAH relative to OC was exponentially and negatively correlated to C/N ratios ( r 2 = 0.67), a measure that often is used for tissue age. In fact, C/N ratios alone explained two-thirds of the variability in OPAH/OC ratios suggesting particularly high retention, sorption, and persistency of OPAHs in old, decomposed carbon fractions.